Ddx18 is essential for cell-cycle progression in zebrafish hematopoietic cells and is mutated in human AML - Payne, Elspeth M. (American Society of Hematology, 2011)
In a zebrafish mutagenesis screen to identify genes essential for myelopoiesis, we identified an insertional allele hi1727, which disrupts the gene encoding RNA helicase dead-box 18 (Ddx18). Homozygous Ddx18 mutant embryos exhibit a profound loss of myeloid and erythroid cells along with cardiovascular abnormalities and reduced size. These mutants also display prominent apoptosis and a G1 cell-cycle arrest. Loss of p53, but not Bcl-xl overexpression, rescues myeloid cells to normal levels, suggesting that the hematopoietic defect is because of p53-dependent G1 cell-cycle arrest. We then sequenced primary samples from 262 patients with myeloid malignancies because genes essential for myelopoiesis are often mutated in human leukemias. We identified 4 nonsynonymous sequence variants (NSVs) of DDX18 in acute myeloid leukemia (AML) patient samples. RNA encoding wild-type DDX18 and 3 NSVs rescued the hematopoietic defect, indicating normal DDX18 activity. RNA encoding one mutation, DDX18-E76del, was unable to rescue hematopoiesis, and resulted in reduced myeloid cell numbers in ddx18(hi1727/+) embryos, indicating this NSV likely functions as a dominant-negative allele. These studies demonstrate the use of the zebrafish as a robust in vivo system for assessing the function of genes mutated in AML, which will become increasingly important as more sequence variants are identified by next-generation resequencing technologies.